Contemporary criticism on the representation of female travellers of the Ottoman harem in the 19th century: a review - Mohd Ramli, Aimillia (IIUM Press, 2011)
A common problem that needs addressing in the study of narratives concerning the Orient and the Ottoman harem in the 19th century, through an emphasis on gender, is the popular belief amongst certain groups in postcolonial and feminist scholarships that writings by women on these subjects are the alternative to hegemonic imperial discourse. Post-colonial and feminist critics whose research deals with women travel writers to the Middle East and North AfricaSara Mills, Reina Lewis, Billie Melman, Susan Meyer and Shirley Fosterhave all argued that since women were not directly involved in the imperial project, their writings on the Orient and the Ottoman harem should be considered as articulating alternative views in colonial narratives. One of the aims of this paper is to present evidence that suggests that narratives by women, as well as those by men, did not necessarily bear a counter-hegemonic imprint. It argues that in most cases, they display, through the attention to gender and race in relation to the Orient and the Ottoman harem, ambivalences that neither completely support nor subvert the imperialist subject.